Pragmatismo linguístico: uma análise da linguagem por roteiros entre a pragmática e o pragmatismo. - Silva, Jorge Francisco da (2021)
The question of meaning in language is one of the central themes of linguistics. However, studies on the construction and interpretation of meaning in language are not as well established as in other disciplines, such as in syntax or in phonology, and research focusing on pragmatic studies is not as readily available when compared to research in other hard-core areas in language sciences. The chief objective of this doctoral thesis is to establish historical and theoretical links between pragmatics and pragmatism through the analysis of the thought of Peirce, James and Dewey in order to identify principles and a better characterization and foundation for the development of a proposal of linguistic pragmatism. Specific objectives include an investigation of the relations between central concepts of pragmatic thinking, such as language and thought, experience, beliefs, habits and action in the formation of meaning, and their contributions for the development of a pragmatic philosophy of language historically based on the views of the founders of classical American pragmatism. As for the methodology, this ch is a bibliographical-exploratory research that will be used to constitute a corpus of the state-of-the-art of the relations between pragmatism and language. As a result, one hopes to establish a dialogue between two landmarks - The Pragmatic and Linguistic Turns - and to integrate the conceptions of language in Peirce, James and Dewey with later contributions from postmodern thought within the language sciences.